Extent and Determinants of Thermogenic Responses to 24 Hours of Fasting, Energy Balance, and Five Different Overfeeding Diets in Humans - Thearle, Marie S. (Endocrine Society, 2013)
CONTEXT: Individual variation in the ability to convert excess calories to heat and the effects of dietary macronutrient composition are unclear. OBJECTIVE: Stability and determinants of the energy expenditure (EE) response to overconsumption were assessed. DESIGN, SETTING, AND PARTICIPANTS: Twenty subjects (75% male) with normal glucose regulation were evaluated during 24 hours each of energy balance, fasting, and 5 different diets with 200% energy requirements in a clinical research unit. INTERVENTIONS: Five 1-day overfeeding diets were given in random order: high carbohydrate (75%) and low protein (3%); high carbohydrate and normal protein (20%); high fat (46%) and low protein; high fat (60%) and normal protein; and balanced (50% carbohydrates, 20% protein). MAIN OUTCOME MEASURES: The 24-hour EE, sleeping EE, and thermic effect of food (TEF) during each diet were measured with a metabolic chamber. Appetitive hormones were measured before and after the diets. RESULTS: The EE response to overfeeding exhibited good intraindividual reproducibility. Similar increases above eucaloric feeding in 24-hour EE (mean 10.7 ± 5.7%, P < .001; range 2.9–18.8%) and sleeping EE (14.4 ± 11.3%, P < .001; range 1.0–45.1%) occurred when overfeeding diets containing 20% protein, despite differences in fat and carbohydrate content, but the EE response during overfeeding diets containing 3% protein was attenuated. The percent body fat negatively correlated with TEF during normal protein overfeeding (r = −0.53, P < .01). Fasting peptide YY negatively correlated with TEF (r = −0.56, P < .01) and the increase in sleeping EE (r = −0.54, P < .01) during overfeeding. CONCLUSIONS: There is an intrinsic EE response to overfeeding that negatively associates with adiposity, although it represents a small percentage of consumed calories.